Kant's anatomy of evil - Anderson-Gold, Sharon, 1947-; Muchnik, Pablo (Cambridge University Press, 2010)
Kant infamously claimed that all human beings, without exception, are evil by nature. This collection of essays critically examines and elucidates what he must have meant by this indictment. It shows the role which evil plays in his overall philosophical project and analyses its relation to individual autonomy. Furthermore, it explores the relevance of Kant's views for understanding contemporary questions such as crimes against humanity and moral reconstruction. Leading scholars in the field engage a wide range of sources from which a distinctly Kantian theory of evil emerges, both subtle and robust, and capable of shedding light on the complex dynamics of human immorality.